2009
DOI: 10.1007/s00234-009-0519-6
|View full text |Cite
|
Sign up to set email alerts
|

Stenting is improving and stabilizing anatomical results of coiled intracranial aneurysms

Abstract: SAC is safe and effective for the treatment of wide-necked IA. Despite unsatisfying immediate aneurysm occlusion, the adjunctive effect of the stent is stabilizing or significantly improving long-term anatomical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 20 publications
2
53
3
1
Order By: Relevance
“…However, in our series, progressive occlusion rates (34 and 33 % of HydroSoft and bare coil, respectively) were lower than previous studies [44][45][46] and showed no significant difference among the two groups. The different results may due to anticoagulation therapies after embolization and different judgment criteria.…”
Section: Discussioncontrasting
confidence: 91%
“…However, in our series, progressive occlusion rates (34 and 33 % of HydroSoft and bare coil, respectively) were lower than previous studies [44][45][46] and showed no significant difference among the two groups. The different results may due to anticoagulation therapies after embolization and different judgment criteria.…”
Section: Discussioncontrasting
confidence: 91%
“…It has been proposed that stent-assisted coiling may decrease the rate of aneurysm recurrence after endovascular embolization. 45 However, to evaluate the real impact of this adjunct on recurrence rates, a study comparing stent-assisted coil embolization with coil embolization alone for matched aneurysms would be necessary. In a series of 46 wide-neck aneurysms treated with adjunctive stent placement reported by Biondi et al, 46 the overall recurrence was 18.2% with a retreatment rate equal to 15.2% at a mean of 8.8 months of followup.…”
Section: Stent-assisted Coil Embolizationmentioning
confidence: 99%
“…4 Furthermore, wide-neck MCA bifurcation lesions can sometimes prove challenging for traditional EVT approaches, and numerous techniques have been developed to address these cases. Simple coil embolization and remodeling techniques, including single-balloon-or multiple-balloon-assisted coiling 5,6 ; the dual-catheter technique 7 ; stent-assisted coiling [8][9][10] ; the "Y-stent placement" technique with and without coiling 11,12 ; the "waffle cone" technique 13,14 ; neck-bridge devices 15,16 ; and intra-aneurysmal flow disrupters 17,18 have all been trialed. Flow-diverter stents (FDSs) have proved feasible, safe, and efficient for the treatment of large and broad-neck carotid siphon aneurysms.…”
mentioning
confidence: 99%